2022
DOI: 10.3390/tropicalmed7100315
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Schistosomiasis without a Microscope: Evaluating Circulating Antigen (CCA, CAA) and DNA Detection Methods on Banked Samples of a Community-Based Survey from DR Congo

Abstract: Detection of Schistosoma eggs in stool or urine is known for its low sensitivity in diagnosing light infections. Alternative diagnostics with better sensitivity while remaining highly specific, such as real-time PCR and circulating antigen detection, are progressively used as complementary diagnostic procedures but have not yet replaced microscopy. This study evaluates these alternative methods for the detection of Schistosoma infections in the absence of microscopy. Schistosomiasis presence was determined ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Our ndings add to previous studies that indicated PCR as a better indicator for S. mansoni infection intensity than the Kato Katz assay and can be used without microscopic examination of stools for parasite eggs [26,27] although less sensitive than CAA [27]. PCR is a more sensitive method of P. falciparum detection compared to microscopy especially at low intensity [28,29].…”
Section: Discussionsupporting
confidence: 65%
“…Our ndings add to previous studies that indicated PCR as a better indicator for S. mansoni infection intensity than the Kato Katz assay and can be used without microscopic examination of stools for parasite eggs [26,27] although less sensitive than CAA [27]. PCR is a more sensitive method of P. falciparum detection compared to microscopy especially at low intensity [28,29].…”
Section: Discussionsupporting
confidence: 65%
“…Real-time PCR based on amplification of the genus-specific ITS-2 sequence of Schistosoma spp. is the molecular assay that has found greater use and standardisation in routine diagnostic practice for schistosomiasis [ 63 ]. Another molecular technique that can be used for diagnosis is the search for cell-free DNA, which can be actively released by the parasite or can be derived from dead or decaying worms [ 64 ].…”
Section: Diagnosismentioning
confidence: 99%
“…The point-of-care-circulating cathodic antigen test (POC-CCA) (Rapid Medical Diagnostics, Pretoria, RSA; currently distributed by ICT International on behalf of Rapid Medical Diagnostics) is a urine-based lateral flow assay that requires no equipment, is easy to read by the naked eye, enables higher throughput and less processing than microscopy, uses the more popular sample of urine rather than stool, and is recommended for the detection of S. mansoni infections [12][13][14], and endorsed by WHO since 2017 [15]. The POC-CCA is more sensitive than Kato-Katz, especially for low-intensity infections [16][17][18][19], but issues exist with batch variation [20], low specificity including in samples from non-endemic areas [21][22][23] and cross-reactivity with other helminths [22], interreader variability especially with trace results, and interpretation of these [24,25], all of which can affect individual diagnoses and prevalence estimates [26]. Improved standardization and quality control is required for the POC-CCA to be more reliable [27], which becomes more important as regions and countries move towards the WHO goal of elimination as a public health problem [28].…”
Section: Introductionmentioning
confidence: 99%